Unexpected diagnosis in not so usual clinical scenarios: Acute promyelocytic leukemia – A tertiary care hospital experience - Gautam, Rashmi; Singh, Sarika; Dhar, Lity; Balhara, Kirti; K Sahi, Puneet; Gupta, Sangeeta (Asian Journal of Medical Sciences, 2023)
Background: Acute promyelocytic leukemia (APL) is a distinct subtype of Acute myeloid leukemia (AML) with arrest in maturation of cells of myeloid series in bone marrow. PML-RARA fusion resulting from t(15;17) translocation forms the genetic basis of this haematological malignancy. Introduction of specific differentiating targeted therapy i.e. All-trans retinoic acid (ATRA) have remarkably improved the outcome of this previously dreaded AML. Aims and Objective: The current study presents five cases of Acute promyelocytic leukemia with unusual presentations followed by effective treatment to revert their adverse outcome. Materials and Methods: In this retrospective evaluation of Acute Myeloid leukemia cases, five cases were included from duration of November 2019 to November 2021. The diagnosis of AMLs was made according to EGIL 1998/WHO 2016 guidelines. Peripheral blood (PB) and bone marrow aspirate (BMA) were stained with Giemsa and cytochemistry included myeloperoxidase (MPO) and periodic acid-schiff (PAS). Results: Five color flowcytometric analyses were performed on BMA and PB samples. Chemotherapy was administered in the patients and follow-up was done. 03/05 patients faced mortality due to rapid disease progression. Conclusion: The fast track clinical course from presentation to the outcome of APL is dreadful for the treating clinician and the heamatopathologist. Cytomorphology and Cytochemistry are as important in rapid recognition of APL as Immunophenotyping and Cytogenetics for establishing accurate diagnosis.